PERSEPSI WISATAWAN TERHADAP STRATEGI BAURAN PEMASARAN KERTHA GOSA SEBAGAI DESTINASI - Made Darmiati (JURNAL KEPARIWISATAAN, 2017)
This study analyzes the perception of tourists to the promotion mix that has been done by Klungkung Regional Tourism Office for the development of cultural attractions Kertha Gosa. The respondents consisted of 100 tourists who come to visit Kertha Gosa. Promotional mix includes advertising, personal selling, public relations, and sales promotion. The average value of promotion strategy consists of advertising, personal selling, public relations, and sales promotion was 3.95, well. Promotional activities on personal selling points scored 4.22, very good. Promotional activities on public relations points scored 4.07, either. Promotional activities at points of sales promotion get a grade 4, good. One of four elements of the promotional mix is valued less than the maximum that is advertising. Although overall the advertising element gets the value of 3.45 included in either category (B) the elements of advertising at the point of advertising on television get a score of 3.03, and advertising through the installation of billboards and banners convenient place to get a score of 3.15 is the score lowest on advertising element.